Antimicrobial Effects of Dental Luting Glass Ionomer Cements on Streptococcus mutans. (23rd March 2014) - Klai, Sina; Altenburger, Markus; Spitzmüller, Bettina; Anderson, Annette; Hellwig, Elmar; Al-Ahmad, Ali
Abstract : Objective . To reduce secondary caries, glass ionomer luting cements are often used for cementing of indirect restorations. This is because of their well-known antimicrobial potential through the release of fluoride ions. The aim of this in vitro study was to investigate the antimicrobial effect of five dental luting cements which were based on glass ionomer cement technology. Methods . Five different glass ionomer based luting cements were tested for their antimicrobial effects on Streptococcus mutans in two different experimental setups: (i) determination of colony-forming units (CFUs) in a plate-counting assay; (ii) live/dead staining (LDS) and fluorescence microscopy. All experiments were conducted with or without prior treatment of the materials using sterilized human saliva. Antimicrobial effects were evaluated for adherent and planktonic bacteria. Bovine enamel slabs (BES) were used as negative control. BES covered with 0.2% chlorhexidine (CHX) served as positive control. Results . Each of the tested materials significantly reduced the number of initially adhered CFUs; this reduction was even more pronounced after prior incubation in saliva. Antimicrobial effects on adherent bacteria were confirmed by live-dead staining. Conclusion . All five luting cements showed an antimicrobial potential which was increased by prior incubation with human saliva, suggesting an enhanced effect in vivo .